Low-temperature supercapacitor - Muhammad Ja'far Sodiq Bin Kelana Izrak (Nanyang Technological University, 2023)
Supercapacitors have emerged as one of the most effective energy storage technologies. Recently, pseudocapacitors have started making waves in the research field. Its fast and reversible faradaic reaction enhances specific capacitance and hence, energy density, which is beneficial for energy storage. However, pseudocapacitors have relatively low power density and cyclic stability.